(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The highly contested doctrine of death sentence distinguishes a procedure where such a heinous crime has been committed that an alternative award of life imprisonment can never be recommended, and the precious action can be classified as the thesis of the rarest of rare theories in the age of punitive multiculturalism. The horrendous philosophical perspectives of the death penalty that were appropriated during the Moghul reign were later adopted by the colonial empire, who carried out the punishment of death penalty by following strict disciplinary judicial formalities, and this particular principle of death penalty was later adopted by the Indian Penal Code. As current criminal law collides with the heavenly views of the world’s most renowned human rights philosophies, calls to limit or abolish the idea of death punishment are growing. In support of the above-mentioned idea, the second optional Protocol to the Covenant on Civil and Political Rights calls for the abolition of capital punishment and supports the expression of a human being’s nobler and magestic characteristics. The ECOSOC resolution and subsequent statements guarantee delinquents facing the death penalty their fundamental rights. The paper emphasizes the essential features of death penalty principles, focuses on the perspectives of the death penalty’s constitution ability and the rarest of rare doctrines, and concludes with a conclusive suggestion that the prospective doctrine of rehabilitative theory is more suitable than the Deterrent philosophy, harmoniously emancipating the possible transformation of a detainee.